Never Call Retreat - Thompson, J. author. aut Link
XI, 362 p.
Keywords: The first modern account of Theodore Roosevelt and the First World War, this is a tale of war and politics as well as the private story of true love and family devotion: a story as multi-faceted as TR's own personality.